(1′RS, 2′SR, 6′RS)-(2, 6-Dihydroxy-4-methoxyphenyl)-[3′-methyl-2′-(3″-methylbut-2″-enyl)-6′-phenyl-cyclohex-3′-enyllmethanone (Panduratin A)- a Constituent of the Red Rhizomes of a Variety of Boesenbergia pandurata - Pittaya Tuntiwachwuttikul (2018)
Spectroscopic studies have established the structure (1′RS, 2′SR, 6′RS)-(2, 6-dihydroxy-4-methoxy-phenyl)[3′-methyl-2′-(3″-methylbut-2″enyl)-6′-phenylcyclohex-3′-enyl]methanone for panduratin A which, together with pinostrobin and two known chalcones, boesenbergin A and rubranine, has been isolated from the red rhizomes of a variety of Boesenbergia pandurata (Roxb.) Schltr. A synthesis of rubranine, in moderate yield, has also been achieved. © 1987, CSIRO. All rights reserved.